Availability of Instructional Materials and Students’ Academic Performance in Public Secondary Schools in Bayelsa State - Dr. Diepreye Okodoko (International Journal of Economics and Financial Management, 2026)
The research examined how instructional materials affect academic achievement in Bayelsa State public secondary schools. The study used correlational survey research. For the 2021/2022 academic year, 18,140 pupils from 88 public secondary schools in three Bayelsa State Local Government Areas were studied. Bayelsa State's Ogbia, Sagbama, and Yenagoa LGAs get 1680, 5211, and 11249. In the 2021/2022 academic year, proportional stratified random selection was used to pick 880 students (4.85% of the total population) from public secondary schools in the three designated Local Government Areas of Bayelsa State, Nigeria. The 10-item Availability of Instructional Materials and Students’ Academic Performance Questionnaire (AIMSAPQ) was utilised to gather data. The research supervisor and two measurement and evaluation specialists from the department of educational foundations, Niger Delta University, Wilberforce Island, Bayelsa State, validated the instrument. Cronbach's Alpha was used to calculate instrument internal consistencies' reliability coefficients. The dependability coefficients for instructional material availability and student performance were.720 and.760. Simple percentage analysis, model summary of simple regression analysis, and PPMC analysis were used in SPSS version 26 to analyse demographic data, research question, and hypothesis. The research found that secondary school pupils' academic performance is affected by instructional materials. The result advised that students rely heavily on instructional resources in their schools to project their secondary school academic success.